The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3354/meps09215
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in the trophic ecology of an avian rocky shore predator, the African black oystercatcher, along the southern African coastline

Abstract: The reflection of baseline isotopic signals along marine food chains up to higher trophic levels has been widely used in the study of oceanic top predators but rarely for intertidal predators. We investigated variation in the δ 13 C and δ 15 N ratios of a sedentary, rocky shore predator, the African black oystercatcher Haematopus moquini, over ~2000 km of the southern African coastline, which is characterized by strong biogeographic patterns in primary productivity and intertidal communities. Blood and feather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 69 publications
(68 reference statements)
3
20
0
Order By: Relevance
“…Sardine displayed the lowest mean δ 15 N values of all fishes (mean ± SD = 9.2‰ ± 0.7), comparable to zooplankton of copepods and euphausiids (mean δ 15 N = 9.6 ± 0.2‰, and 9.7 ± 1.2‰, respectively). When considering +3.4‰ per trophic level from the baseline of mytilid bivalves from Kohler et al. (2011, mean δ 15 N = 9.2‰), with the exception of Synagrops sp., all hake (both M. paradoxus and M. capensis ) >20 cm in total length had δ 15 N values above zooplankton and nekton prey, and generally had TLs of 3.0–3.8 (Table 1, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sardine displayed the lowest mean δ 15 N values of all fishes (mean ± SD = 9.2‰ ± 0.7), comparable to zooplankton of copepods and euphausiids (mean δ 15 N = 9.6 ± 0.2‰, and 9.7 ± 1.2‰, respectively). When considering +3.4‰ per trophic level from the baseline of mytilid bivalves from Kohler et al. (2011, mean δ 15 N = 9.2‰), with the exception of Synagrops sp., all hake (both M. paradoxus and M. capensis ) >20 cm in total length had δ 15 N values above zooplankton and nekton prey, and generally had TLs of 3.0–3.8 (Table 1, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…, 2008). Our use of bivalves from Kohler et al. (2011) as the δ 15 N base was based on its TL proximity to zooplankton (size 200–500 μm) in our study and that of Sholto‐Douglas et al.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have examined the isotopic values of feathers and blood synthesized under the same diet (Sanpera et al 2007;Bugoni et al 2008;Quillfeldt et al 2008;Kohler et al 2011;Cruz et al 2012;Cherel et al 2014). Based on a metaanalysis of these studies, we used the following regressions from Cherel et al (2014) to standardize values to directly compare between δ 15 N and δ 13 C values obtained from the feather and blood tissues of the same individual penguin:…”
Section: Standardizing Stable Isotope Values Between Blood and Feathersmentioning
confidence: 99%
“…Unfortunately, no stable isotope data are available for these areas. Studies conducted from the primary producers up to top predators showed an increase in  15 N along the southern African coastline from the east coast up to Namibia reflecting the differences in oceanography and coastal hydrography (Hill et al 2006;Hill and McQuaid 2008;Kohler et al 2011). The oceanography and hydrography in the Gulf of Guinea and along the Angola coastline are complex (Rouault et al 2007;Rouault 2012), so one would expect variations in the  13 C and  15 N along the western African coast; variations that would be detected in the tern feathers.…”
Section: Wintering Strategy Of the Eastern Cape Damara Tern Populationmentioning
confidence: 92%